(untitled) (MAUSAM, 2025)
The article describes the developments that led to the establishment of the Surface meteorological Observation systems in India Meteorological Department (IMD). IMD is continuing upgrade & modernize the surface meteorological instrument network through the last 150 years in the service of the nation.